1998
DOI: 10.1111/1467-839x.00010
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Individualism vs. Collectivism to Cross‐national Differences in Display Rules

Abstract: Despite the fact that display rules are an important concept of theories of emotion and contemporary psychology, relatively little cross-cultural research has been done on them. This study examined cross-national differences in display rules of emotion, and investigated the degree to which those differences could be attributed to Individualism and Collectivism (IC) measured on the individual level. Participants in the US, Japan, South Korea, and Russia completed a comprehensive measure of display rules assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
185
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(208 citation statements)
references
References 28 publications
16
185
1
6
Order By: Relevance
“…The model thus suggests that the Japanese participants have had less prior exposure to angry faces than their American counterparts. This would be consistent with the concept of display rules discouraging the expression of negative emotions in Japanese culture (see, e.g., Matsumoto et al, 1998). Looking more closely at the behavioral data, we see that Japanese participants were less accurate than U.S. participants on anger overall, but they were more accurate than U.S. participants on the JAFFE anger stimuli.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The model thus suggests that the Japanese participants have had less prior exposure to angry faces than their American counterparts. This would be consistent with the concept of display rules discouraging the expression of negative emotions in Japanese culture (see, e.g., Matsumoto et al, 1998). Looking more closely at the behavioral data, we see that Japanese participants were less accurate than U.S. participants on anger overall, but they were more accurate than U.S. participants on the JAFFE anger stimuli.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have found these dimensions diagnostic for explaining differences between broad cultural groups and individuals (Gudykunst & TingToomey, 1988;Matsumoto, 1990;Matsumoto et al, 2002;Matsumoto, Kudoh, & Takeuchi, 1996;Matsumoto, Takeuchi, Andayani, Kouznetsova, & Krupp, 1998;Tanako & Osaka, 1999).…”
Section: Cultural Differences In Facial Expression Interpretationmentioning
confidence: 99%
“…Our hypothesis (2) was partially supported as individuals reporting more collectivism revealed less negative emotion, however no relationship to positive emotion was found. This highlights the cultural display rule that while positive emotion is viewed as a constructive emotion regardless of culture; within collective in-groups negative emotions like disgust are considered destructive and should be suppressed (Markus & Kitayama, 1991;Matsumoto, Takeuchi, Andayani, Kouznetsova, & Krupp, 1998). This norm appeared to affect negative expressivity overall as collectivism predicted fewer disgust expressions, even when controlling for suppression condition.…”
Section: Discussionmentioning
confidence: 85%
“…For example, cultural differences in the communication of emotional intensity could reflect the operation of culture-specific display rules (25) on the transmission (and subsequent experience) of facial expressions in each cultural context. For example, East Asian models of fear, disgust, and anger show characteristic early signs of emotional intensity with the eyes, which are under less voluntary control than the mouth (26), reflecting restrained facial behaviors as predicted by the literature (27). Similarly, culture-specific dialects (28) or accents (29) would diversify basic facial expression signals across cultures, giving rise to cultural hallmarks of facial behavior.…”
Section: Discussionmentioning
confidence: 99%